Studi karakteristik sub kronis limbah bahan berbahaya dan beracun fly ash industri pulp dan kertas PT. Riau Andalan Pulp and Paper - Jailani Jailani; Aras Mulyadi; Rahmat Karnila (Pelantar Press, 2018)
Sub chronic Characteristics Study of Hazardous waste fly ash Pulp and Paper Industry PT Riau Andalan Pulp and Paper aimed to observed hazardous waste characteristics, both physical or toxically characteristics (TCLP, LD50, and Sub chronic), to observe the influence of fly ash doses to mice trough toxic sub chronic characteristics tes . The research methods used survey and experimental method. Survey method is used to analyze certificate of analysis data from fly ash characteristic tesed .Experimental method is used for sub chronic tes to mice animals tes in 90 days with dosage, control (0 mg/kg body weight ), low (5 mg/kg body weight), medium (50 mg/kg body weigh), and high (500 mg/kg body weight). Results of this research showed that fly ash from Pulp and Paper Industry PT RAPP passed characteristics tes of explosive, flammable, reactive and toxic characteristics (TCLP, LD50, and Sub chronic). Dosage of fly ash level in 0 mg/kg body weight, 5 mg/kg body weight, 50 mg/kg body weight, 500 mg/kg body weight for 90 days are not influences for increasing the weight of mice body, food and beverage intake, metabolism of carbohydrates, proteins and fats, hematology and NOAEL value is over 500 mg/kg weight of body. Based on this research had been concluded that fly ash from Pulp and Paper Industry PT RAPP not identified as hazardous waste and can be submitted to KLHK for do exceptions study as hazardous waste in accordance with article 191 PP 101 Year 2014.